SIX-STROKE ROTARY INTERNAL COMBUSTION ENGINE - MILLY, Miron (Trends in education, 2008)
The paper is describing construction and function of six-stroke toroidal rotary internal combustion engine, with rotating movement of two pistons. The engine consist of the working case, two rotary pistons and of the control mechanism, by which is ruled the rotating movement of the both pistons, gliding situated at the toroidal working case.
Keywords: six-stroke (six-cycle) combustion engine; toroidal; rotary; piston